Writing: Unit-Lessons in Composition - Brown, Don P. (Palo Alto Ginn and Company, 1964)
Each chapter is essentially a lesson about a certain writing skill or technique. Each is brief enough that you may be able to understand it, work with it, and then write using that new skill.
Keywords: Writing